Pancreatic cancer incidence and survival and the role of specialist centres in resection rates in England, 2000 to 2014: a population-based study - Exarchakou, Aimilia; Papacleovoulou, Georgia; Rous, Brian; Magadi, Winnie; Rachet, Bernard; Neoptolemos, John P.; Coleman, Michel P. (Pancreatology, 2020)
Background - The aim was to compare population-based survival for exocrine pancreatic cancer in England in the 23 regions covered by specialist centres. The centres were initiated in 2001, covering populations of 2-4 million. - Methods - We examined incidence for adults diagnosed with a pancreatic exocrine cancer during 1995-2014 and age-standardised net survival up to five years after diagnosis for patients diagnosed during 2000-2013. We examined variation in regional resection rates and survival for patients diagnosed during 2010-2013. The data were extracted from the National Cancer Registration and Analysis Service. - Results - Age-standardised annual incidence rates of exocrine pancreatic cancer increased from 17.1 per 100,000 during 1995-1999 to 18.7 during 2010-2014. Age-standardised one-year and five-year net survival increased from 17.9% and 3.6%, respectively, for 2000-2009, to 21.6% and 4.2% during 2010-2013. There were 2086 (8.9%) resections among 23,415 patients diagnosed with an exocrine tumour in 2010-2013. The proportion ranged from 5.1% to 19.6% between centres. Among resected patients, survival was 73.0% at one year and 20.2% at five years. Of the total 2118 resected patients, 18 (0.9%) were at stage 1; 34 (1.6%) at stage 2; 791 (37.3%) at stage 3 and 140 (6.6%) at stage 4, although 53.6% of stage information was missing. Five-year survival was 2.1% for those who were not resected. The number of resections performed in each centre was not correlated with one-year survival. - Conclusions - Despite improvements in the management of pancreatic cancer in England with the introduction of specialist centres, resection rates remain relatively low, and survival remains lower than in comparably wealthy countries.
Gesehen am 10.06.2020